Assessment of vitamin D level in the umbilical cord blood of the Arkhangelsk city infants born in winter time - S. I. Malyavskaya; V. G. Karamyan; G. N. Kostrova; A. V. Lebedev; С. И. Малявская; В. Г. Карамян; Г. Н. Кострова; А. В. Лебедев (Rossiyskiy Vestnik Perinatologii i Pediatrii (Russian Bulletin of Perinatology and Pediatrics), 2018)
Forthe child’s optimal growth and development, the normal provision with vitamin D isrequired. The vitamin D levelsin newborn depend directly on the mother’s provision with this vitamin, who is a single vitamin source for the child. The purpose of the study is to assess the provision with vitamin D in newborns of Arkhangelsk city in winter. 25(ОН)D determination in the blood serum of 55 newborns and their mothers was carried out using the method of the enzyme-linked immunosorbent assay at the laboratory of Arkhangelsk Children’s Regional Clinical Hospital. Resulting from the test carried out, only 4 (7%) children had the normal level of vitamin D, 36% (20 children) had the level corresponding to the deficiency: 14 (26% children) had the insufficiency of this vitamin, 17 (31% children) had a severe deficiency. The data obtained indicate the necessity to optimize the activities on the vitamin D deficiency prophylaxis in the pregnant women and support the prescription of vitamin D drugs to the newborns of Arkhangelsk city from the first days of the life. Для оптимального роста и развития ребенка необходима нормальная обеспеченность витамином D. Уровень витамина D у новорожденного ребенка напрямую зависит от обеспеченности этим витамином матери, являющейся для него единственным источником витамина. Цель исследования: оценить обеспеченность витамином D новорожденных г. Архангельска, рожденных в зимний период. Определение 25(ОН)D в сыворотке крови 55 новорожденных и их матерей проводили методом иммуноферментного анализа в лаборатории Архангельской детской областной клинической больницы. В результате проведенного исследования только у 4 (7%) детей отмечен нормальный уровень витамина D, 20 (36%) детей имели уровень, соответствующий дефициту: у 14 (26%) детей выявлена недостаточность этого витамина, у 17 (31%) – тяжелый дефицит. Полученные данные свидетельствуют о необходимости оптимизации мероприятий по профилактике дефицита витамина D у беременных женщин и обосновывают назначение препаратов витамина D новорожденным ...